Consensus statement on injury definitions and data collection procedures in studies of football (soccer) injuries. Issue 3 (27th February 2006) - Fuller, C W; Ekstrand, J; Junge, A; Andersen, T E; Bahr, R; Dvorak, J; Hägglund, M; McCrory, P; Meeuwisse, W H
Abstract : Variations in definitions and methodologies have created differences in the results and conclusions obtained from studies of football (soccer) injuries, making interstudy comparisons difficult. Therefore an Injury Consensus Group was established under the auspices of Fédération Internationale de Football Association Medical Assessment and Research Centre. A nominal group consensus model approach was used. A working document on definitions, methodology, and implementation was discussed by the group. Iterative draft statements were prepared and circulated to members of the group for comment before the final consensus statement was produced. Definitions of injury, recurrent injury, severity, and training and match exposures in football together with criteria for classifying injuries in terms of location, type, diagnosis, and causation are proposed. Proforma for recording players' baseline information, injuries, and training and match exposures are presented. Recommendations are made on how the incidence of match and training injuries should be reported and a checklist of issues and information that should be included in published reports of studies of football injuries is presented.